Understanding teamwork experiences of neurodivergent students: A phenomenological exploration of conflict and collaboration in engineering teams - McKenna P. Sperry; Thomas A. O’Neill (PLoS ONE, 2026)
Neurodivergent individuals have been systematically excluded from employment opportunities, meaning that we know little about lived experiences within neurodiverse teams. To fill this gap, the current phenomenological study seeks to understand the teamwork experiences of neurodivergent students at the University of Calgary. We conducted semi-structured interviews with students in the faculty of engineering who self-identify as neurodivergent, exploring their perceptions and experiences of teamwork and conflict. We grouped the themes that emerged from the interview data into cognitive and behavioural dimensions to represent what neurodivergent students think and do as they face and manage challenges and opportunities within team settings. Together, the themes highlight that students’ desire to be understood and recognized by others significantly influences their team interactions. These findings suggest that traditional theories attempting to explain the social elements of neurodivergence are limited in their capacity to capture the nuanced ways in which neurodivergent individuals seek to understand and relate to others, particularly in team contexts. Finally, this study translates students’ insights into recommendations for educators to create more supportive and inclusive teamwork environments in courses.